Pengembangan Bisnis Digital Berbasis Software As A Service (SAAS): Studi Kasus Platform Pengelolaan Zakat “Catat Zakat” Di Pt Titik Terang Teknologi - Ekky Fauzan Maulana; Keni Kaniawati (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to develop a comprehensive business plan for the Catat Zakat Software as a Service (SaaS) platform, analyze business development planning across multiple aspects, and evaluate financial investment feasibility. Catat Zakat is a B2B SaaS platform developed by PT Titik Terang Teknologi to help Zakat Management Institutions (LAZ) automate zakat management from collection to distribution. The research employs a qualitative descriptive method with a single case study approach, involving semi-structured interviews with 25 LAZ managers in West Java, DKI Jakarta, and East Java. The analytical framework integrates Design Thinking, Business Model Canvas, SWOT-TOWS analysis, Timmons Model, and financial feasibility analysis (NPV, IRR, Payback Period, Profitability Index). Results show that 92% of LAZ still prepare PSAK 109 reports manually, 88% face multi-channel reconciliation difficulties, and 84% lack adequate donor tracking systems. The Timmons Model evaluation yields a score of 4.11/5.00 (Highly Attractive Opportunity). Financial feasibility analysis under the moderate scenario shows NPV of IDR 8.7 billion, IRR of 42%, Payback Period of 4.8 years, and Profitability Index of 2.71 — all metrics exceeding minimum feasibility standards.